ESTIMATION OF DIVERSITY AND GENETIC PARAMETERS OF TEN GENOTIES OF LARGE CHILE (Capsicum annuum L) - Lagiman, Lagiman; Supriyanta, Bambang (Universitas Pembangunan Nasional Veteran Yogayakarta, 2021)
Chili (Capsicum annuum L.) is one of the horticultural commodities that have high economic value which is used as vegetables or cooking spices, industrial raw materials, and has export opportunities. The development of superior chili varieties requires a large variety of germplasm that can be used as parents to be crossed with each other to obtain new superior traits. One of the efforts to determine the diversity of plants is to characterize the morphology and production. The purpose of this study was to obtain distinguishing characters among ten genotypes of large chilies, to determine the value of genetic parameter estimators for several genotypes of large chilies and to identify important characters that influence the yield of large chili genotypes. The study was a single factor field experiment in the form of 10 large chili genotypes arranged in a Randomized Completely Block Design (RCBD) with 3 blocks as replication. Genotypes of large chili are: Pilar, Arimbi, Baja, Panex, Forever, Columbus, Gada, Dewa, Rengku, Beautiful. Observation variables are plant height, stem diameter, number of leaves, width of leaves, leng of leaves, flowering age, harvest age, fruit length, fruit weight per plant, fruit diameter, and weight of fruit.. Chili characters that show high genetic diversity are leaf width, while high phenotypic diversity is in fruit weight parameters. High heritability values were found in the characters of flowering age, harvest age, and fruit diameter.